Embodying architectures Body extensions and forms in hybrid environments (Itinera, 2023)
This article aims to describe the situated interactions between humans and hybrid architectures composed of physical and digital elements. Using a post-phenomenological perspective and drawing on case studies from everyday life and contemporary new media art, the paper will first discuss the limits and possibilities of this philosophical approach. Specifically, post-phenomenology has limitations in describing the technologies present in hybrid architecture that are becoming increasingly transparent and capable of manipulating the habitat while being embodied in the user and widespread in the environment. Through a genealogical reconstruction of the concept of form in Wolfgang Köhler, Kurt Goldstein, and Maurice Merleau-Ponty, the article will explore the continuity between endosomatic and esosomatic space, providing new tools for the post- phenomenological debate.